Search Result Prefetching Using Cursor Movement - Diaz, Fernando; Guo, Qi; White, Ryen W. (39th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2016), July 17-21, 2016, Pisa, Italy, 2016)
Search result examination is an important part of searching. High page load latency for landing pages (clicked results) can reduce the efficiency of the search process. Proactively prefetching landing pages in advance of clickthrough can save searchers valuable time. However, prefetching consumes resources that are wasted unless the prefetched results are requested by searchers. Balancing the costs in prefetching particular results against the benefits in reduced latency to searchers represents the search result prefetching challenge. We present methods that leverage searchers' cursor movements on search result pages in real time to dynamically estimate the result that searchers will request next. We demonstrate through large-scale log analysis that our approach significantly outperforms three strong baselines that prefetch results based on (i) the search engine result ranking, (ii) past clicks from all searchers for the query, or (iii) past clicks from the current searcher for the query. Our promising findings have implications for the design of search support that makes the search process more efficient.